FINNISH KULLERVO AND CHINESE KUNGFU - Chen, Chapman (POLISSEMA – Revista de Letras do ISCAP, 2019)
Introduction: There are many important Finnish plays but, due to language barrier, Finnish drama is seldom exported, particularly to Hong Kong and China. Objective: To find out differences in mentality between the Finnish and Chinese peoples by comparing the partially localized Chinese translation of Aleksis Kivi’s tragedy, Kullervo, with genuine Chinese martial arts literature. Methodology: 1. Chapman Chen has translated the Finnish classic, Kullervo, directly from Finnish into Chinese and published it in 2005. 2. In Chen's Chinese translation, cultural markers a re domesticated. On the other hand, values, characterization, plot, and rhythm remain unchanged. 3. According to Gideon Tory, the translator has to strike a golden mean between the norms of the source language and the target language. 4. Lau Tingci lists and explicates the essential components of martial arts drama. 5. According to Ehrnrooth s “Mentality”, equality is the most important value in Finnish culture. Findings: i. Finland emphasizes independence while China emphasizes bilateral relationships. ii. The Finnish people loves freedom, but Gai Sizung argues that the Chinese e Finnish people loves freedom, but Gai Sizung argues that the Chinese people is slavish. iii. Finns are mature while many Chinese are, according to Sun LungFinns are mature while many Chinese are, according to Sun Lung--kee (“The Deep Structure of Chinese CultureDeep Structure of Chinese Culture”; “The Deep Structure of Chinese Sexuality”), fixated at the oral and anal stages. iv. Finnish society highly values equality while Chinese interpersonal relationships are extremely complicated and hierachical. If Kullervo were a genuine Chinese kungfu story, the plot would be much more convoluted. Conclusion: The differences between Finnish and Chinese mentalities are so significant that partially localized or adapted Chinese translations of Finnish drama may still be able to introduce Finnish culture to the Chinese audience.